A high-strength, tough, lightweight, multi-component refractory intermetallic compound and its preparation method
By designing the elemental ratio and process processing of Zr, Ti, Nb, Al and Ta in intermetallic compounds, the problems of brittleness and difficulty in processing at room temperature are solved, and high strength, low density and good pulling are achieved Extension performance, suitable for high-temperature structural materials.
Patent Information
- Application Number
- CN202311700003.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-12-12
- Publication Date
- 2024-12-20
- Estimated Expiration
- 2043-12-12
AI Technical Summary
The existing intermetallic compounds have brittleness and poor processing deformation ability at room temperature, which limits their practical application, especially in high-temperature structural materials, which is difficult to achieve effective deformation processing.
High-strength, tough, lightweight, multi-component refractory intermetallic compounds are prepared using five elements: Zr, Ti, Nb, Al and Ta. The mixture is processed through specific atomic percentage ratios and processes, such as smelting and cold rolling under vacuum or inert gas protection. and annealing treatment to form a B2 structure to achieve high yield strength and tensile extension properties of the alloy.
It realizes high yield strength and tensile elongation at room temperature of lightweight multi-component refractory intermetallic compounds, simplifies processing technology, reduces energy consumption and cost, and significantly improves high-temperature corrosion resistance, and is suitable for aerospace, etc. High temperature structural material.
Smart Images

Figure CN117926098B_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the field of metal materials and their preparation, and relates to a new alloy material and its preparation method, specifically a high-strength, tough, lightweight, multi-component refractory intermetallic compound and its preparation method. At room temperature, the intermetallic compound has low density, high yield strength and excellent tensile ductility. Background Art
[0002] The rapid development of high-tech fields such as aerospace and aviation is closely linked to the design and development of high-temperature structural materials. From the launch of the "Two Machines" major project to vigorously develop the aeroengine and gas turbine industries to the emphasis on the development of aerospace and aviation components, this has led to higher performance requirements for high-temperature structural materials used in next-generation gas turbines and aeroengine endpieces. Intermetallic compounds are widely used as high-temperature strengthening phases in high-temperature structural materials. For example, TiAl-based intermetallic compounds exhibit low density, high elastic modulus, and excellent high-temperature strength, creep resistance, and oxidation resistance. They can be used to manufacture various high-temperature structural components such as compressor and gas turbine blades and blisks. They can partially replace nickel-based superalloy shells, reducing weight by 30-50%. Ti2AlNb alloy, the primary strengthening phase, is strengthened by intermediate compounds. While Ti2AlNb alloy exhibits excellent high-temperature performance due to its mixed metallic and covalent bonding, it also exhibits inherent brittleness and low room-temperature plasticity in its solidified structure, making it difficult to process. This significantly limits its practical application and makes the alloy incapable of room-temperature deformation. How to improve the room temperature brittleness of intermetallic compounds and enhance their processing deformation capabilities has always been a core issue that needs to be solved urgently. Summary of the Invention
[0003] The purpose of this section is to summarize some aspects of the embodiments of the present invention and briefly introduce some preferred embodiments. Some simplifications or omissions may be made in this section and the abstract and title of this application to avoid obscuring the purpose of this section, the abstract and the title of the invention, and such simplifications or omissions should not be used to limit the scope of the present invention.
[0004] In view of the above problems and / or the problems existing in the prior art, the present invention is proposed.
[0005] One of the objects of the present invention is to provide a high-strength, lightweight, multi-component refractory intermetallic compound.
[0006] In response to the problems of existing refractory metals such as high density, poor room temperature plasticity and difficulty in deformation processing, the present invention provides a high-strength, tough and lightweight multi-component refractory metal compound and a preparation method thereof, aiming to solve the problems of poor room temperature plasticity and poor deformability of multi-component refractory metals. It has the advantages of easy preparation, convenient deformation processing, and large-scale preparation.
[0007] The present invention selects five elements, Zr, Ti, Nb, Al and Ta, to prepare an alloy based on considerations of economic cost, weight reduction requirements and properties of each component. The alloy has an intermetallic compound B2 structure in any state. The alloy comprises, by atomic percentage, 30-34.0% Zr, 27.0-31.0% Ti, 17.0-22.0% Nb, 9.0-15.0% Al and 5.0-8.0% Ta.
[0008] The sum of the atomic percentages of Zr, Nb, Ti, and Ta is ≤92.0% and ≥80%; the sum of the atomic percentages of each component is 100%.
[0009] As a preferred embodiment of the high-strength, tough, lightweight, multi-component refractory intermetallic compound of the present invention, the alloy is composed of the following components, calculated in atomic percentage: Zr 31.5-34.0%, Ti 27.0-30.0%, Nb 17.0-20.5%, Al 9.0-15.0%, and Ta 6.0-8.0%.
[0010] As a preferred embodiment of the present invention, a high-strength, tough, lightweight, multi-component refractory intermetallic compound is provided, wherein: the alloy is composed of the following components, calculated in atomic percentage: Zr 32.75-33.5%, Ti 28.25-29%, Nb 18.75-19.5%, Al 11-13%, and Ta 6.75-7.2%. It should be noted that due to errors and other reasons, the alloy composition range fluctuates within a certain range and still falls within the scope of protection of this patent.
[0011] As a preferred embodiment of the present invention, a high-strength, tough, lightweight, multi-component refractory intermetallic compound has the following characteristics:
[0012] (a) The alloy has an intermetallic compound B2 structure in any state;
[0013] (b) The density of the alloy is 6.2~7.0 g / cm 3 ; The density of the preferred alloy is 6.6~6.8 g / cm 3 ;
[0014] (c) The lightweight multi-component refractory intermetallic compound has a tensile yield strength of 900 to 1400 MPa at room temperature; preferably, the tensile yield strength is 1000 to 1250 MPa;
[0015] (d) The tensile elongation of the lightweight multi-component refractory intermetallic compound at room temperature is 5% to 45%; preferably, the tensile elongation is 35% to 40%.
[0016] It should be noted that when preparing the alloy according to the atomic percentage of the present invention, due to the purity of the raw materials and the defects in smelting and preparation that reduce the plastic strength of the alloy, the plasticity of the alloy fluctuates within a certain range and should be protected by this patent.
[0017] Another object of the present invention is to provide a method for preparing a high-strength, tough, lightweight, multi-component refractory intermetallic compound, comprising weighing the components according to the atomic ratio of the alloy, melting them under vacuum or inert gas protection conditions, casting them, cold-rolling the cast alloy, and then annealing them under vacuum or protective atmosphere.
[0018] As a preferred embodiment of the method for preparing a high-strength, tough, lightweight, multi-component refractory intermetallic compound of the present invention, the raw materials include Nb, Ti, Zr, Al, and Ta particles with a purity of ≥99.50 wt%, which are weighed according to the molar ratio of the above components, polished and cleaned to remove surface dirt and impurities, and finally dried for use.
[0019] As a preferred embodiment of the method for preparing a high-strength, tough, lightweight, multi-component refractory intermetallic compound of the present invention, the raw materials are placed in the order of Al, Ti, Zr, Nb, and Ta; vacuum is applied (≥1×10 -1 Pa), repeat several times; fill with protective gas to 0.000001~0.05 MPa.
[0020] As a preferred embodiment of the method for preparing a high-strength, tough, lightweight, multi-component refractory intermetallic compound of the present invention, before smelting the sample, an additional Ti ingot pre-placed in the furnace can be melted for 1 to 5 minutes to consume residual oxygen and nitrogen in the smelting furnace.
[0021] As a preferred solution of the preparation method of a high-strength, tough, lightweight, multi-component refractory intermetallic compound of the present invention, the smelting is repeated multiple times, which can be supplemented by electromagnetic stirring technology to ensure that the alloy is fully mixed. When smelting the sample, the circulating water cooling system is turned on and it is observed whether the condenser tubes are completely immersed in the circulating cooling water to dissipate heat.
[0022] As a preferred embodiment of the method for preparing a high-strength, tough, lightweight, multi-component refractory intermetallic compound of the present invention, multiple cold rolling passes can be performed in the cast state, with a single-pass rolling reduction of ≤20% and a total rolling reduction of 20% to 100%.
[0023] As a preferred embodiment of the preparation method of a high-strength, tough, lightweight, multi-component refractory intermetallic compound of the present invention, annealing treatment is performed in a vacuum or inert gas atmosphere at an annealing temperature of 800-1250°C for 5-60 minutes, followed by immediate quenching to obtain a uniformly structured intermetallic compound alloy.
[0024] Compared with the prior art, the present invention has the following beneficial effects:
[0025] (1) The present invention realizes lightweight multi-component refractory intermetallic compounds, which can be directly cold-rolled and annealed at room temperature to achieve microstructure control, are conducive to deformation processing, and can realize the preparation of large-scale samples.
[0026] (2) The present invention provides a high-strength, tough, lightweight, multi-component refractory intermetallic compound. The alloy is mainly composed of refractory elements Zr, Ti, Nb, and Ta, and the oxidizing element Al is added. It is very easy to form a dense oxide film or passivation protective layer on the surface of the alloy, which preferentially hinders the diffusion rate of oxygen atoms and significantly improves the high-temperature corrosion resistance of the alloy. It is expected to become a new generation of high-temperature structural materials.
[0027] (3) The present invention provides a high-strength, tough, lightweight, multi-component refractory intermetallic compound with uniform structure. It does not require intermediate annealing treatment and can be directly subjected to large deformation cold rolling to control the structure. The process flow is simple and significantly reduces energy consumption and costs. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the following briefly introduces the drawings required for describing the embodiments.
[0029] Figure 1 Example 1 Zr 33.5 Ti 28.5 Nb 19.0 Al 12 Ta 7.0 Scanning electron micrograph of a lightweight multi-component refractory intermetallic compound after 90% homogenization treatment by cold rolling.
[0030] Figure 2 Example 1 Zr 33.5 Ti 28.5 Nb 19.0 Al 12 Ta 7.0 XRD pattern of lightweight multi-component refractory intermetallic compound after 90% homogenization treatment by cold rolling.
[0031] Figure 3 Example 1 Zr 33.5 Ti 28.5 Nb 19.0 Al 12 Ta 7.0 High-resolution and selected-area electron diffraction patterns of a lightweight multi-component refractory intermetallic compound after 90% homogenization treatment by cold rolling.
[0032] Figure 4 Example 1 Zr 33.5 Ti 28.5 Nb 19.0 Al12 Ta 7.0 Tensile engineering stress-engineering strain curves of a lightweight multi-component refractory intermetallic compound after 90% homogenization treatment by cold rolling.
[0033] Figure 5 Example 2 Zr 33.5 Ti 28.5 Nb 19.0 Al 12 Ta 7.0 Scanning electron micrograph of a lightweight multi-component refractory intermetallic compound after 70% homogenization treatment by cold rolling.
[0034] Figure 6 Example 2 Zr 33.5 Ti 28.5 Nb 19.0 Al 12 Ta 7.0 Tensile engineering stress-engineering strain curves of a lightweight multi-component refractory intermetallic compound after 70% homogenization treatment by cold rolling.
[0035] Figure 7 Example 3 Zr 32.75 Ti 28.25 Nb 18.75 Al 13 Ta 6.75 Scanning electron micrograph of a lightweight multi-component refractory intermetallic compound after 80% homogenization treatment by cold rolling.
[0036] Figure 8 Example 3 Zr 32.75 Ti 28.25 Nb 18.75 Al 13 Ta 6.75 XRD patterns of lightweight multi-component refractory intermetallic compounds after 80% homogenization treatment by cold rolling.
[0037] Figure 9 Example 3 Zr 32.75 Ti 28.25 Nb 18.75 Al 13 Ta 6.75 Tensile engineering stress-engineering strain curves of lightweight multi-component refractory intermetallic compounds after 80% homogenization treatment of cold rolling.
[0038] Figure 10 Example 4 Zr 33.3 Ti 29.0 Nb 19.50 Al 11 Ta 7.2 Scanning electron micrograph of a lightweight multi-component refractory intermetallic compound after 80% homogenization treatment by cold rolling.
[0039] Figure 11 Example 4 Zr 33.3 Ti 29.0 Nb 19.50 Al 11 Ta 7.2 XRD patterns of lightweight multi-component refractory intermetallic compounds after 80% homogenization treatment by cold rolling.
[0040] Figure 12 Example 4 Zr 33.3 Ti 29.0 Nb 19.50 Al 11 Ta 7.2 Tensile engineering stress-engineering strain curves of a lightweight multi-component refractory intermetallic compound after 90% homogenization treatment by cold rolling.
[0041] Figure 13 Comparative Example 1 Zr 31.0 Ti 28.0 Nb 19 Al 16 Ta 6.0 Macroscopic morphology of lightweight multi-component refractory intermetallic compounds after rolling. DETAILED DESCRIPTION
[0042] In order to make the purpose, technical solutions and advantages of the present invention more clear, the present invention is further described in detail with reference to the embodiments. The protection scope of the present invention is not limited to the following specific embodiments, and any equivalent substitution based on the embodiments of the present invention falls within the protection scope of the present invention.
[0043] All raw materials in the examples of this application were obtained through commercial channels. Example 1
[0044] This embodiment designs a high-strength, light-weight, multi-component refractory intermetallic compound with the chemical formula Zr 33.5 Ti 28.5 Nb 19.0 Al 12 Ta 7.0 (atomic percentage), the preparation steps are as follows:
[0045] (1) Raw material pretreatment: Zr, Nb, and Ta particles with a purity of ≥99.90 wt%, and Ti and Al particles with a purity of 99.95 wt% were polished and ultrasonically cleaned at room temperature for 30 min to remove surface dirt and impurities, and finally placed in a drying oven for drying.
[0046] (2) Raw material ratio: by converting the molar percentage and mass percentage of the multi-component refractory intermetallic compound, based on 100g of alloy, 39.321g, 17.609g, 22.933g, 4.167g and 16.060g of each metal raw material were weighed according to Zr, Ti, Nb, Al and Ta, respectively.
[0047] (3) Melting: Place the raw materials weighed in step 2 into the water-cooled copper crucible of the vacuum arc furnace in order of melting point. Note that the Al particles with low melting point are placed at the bottom. Vacuum to 5×10 -3 Pa, repeated three times; filled with argon to 0.05 MPa as a protective atmosphere; before melting, melt the extra Ti ingots pre-placed in the furnace for 2 minutes to consume the residual oxygen and nitrogen in the melting furnace. The melting current was 330A and the melting time was 120 seconds; start melting the alloy ingots, and melt them repeatedly for 8 times. The melting current was controlled at 390A. Each melting arc should last for 7 minutes and be supplemented by electromagnetic stirring technology. The current frequency was 7Hz to ensure that the alloy was fully mixed.
[0048] (4) Casting: The uniformly smelted alloy obtained in step 3 is placed in a water-cooled copper mold of 80×30×10 mm in a vacuum arc furnace for remelting and molding. After the sample is cooled, the sample is taken out. The specific operation is: vacuum to 5×10 -3 Pa, repeated three times; filled with argon to 0.05 MPa as a protective atmosphere; melted the extra Ti ingots pre-placed in the furnace before smelting, the melting current was 330A, and the melting time was 120 seconds; started to melt the alloy ingot, and repeated the melting 4 times, the melting current was controlled at 390A, and the arc should last for 8 minutes each time.
[0049] (5) Cold rolling annealing: The cast alloy obtained in step 4 was cut into 10.00 mm thick strip samples, with a single-pass rolling reduction of ~8% and a total rolling reduction of 90%. The rolled sample was placed in a quartz tube for sealing, and the quartz tube was first vacuumed to 3×10 -3 Pa, and then filled with argon to maintain the pressure in the tube at 0.003 MPa. After the sealing is completed, the sample is kept at 900 ° C for 15 minutes and then immediately water quenched; the sample is cut into 1.65 × 7.5 × 21 mm dog bone tensile specimens by wire cutting, and polished on 180#, 400#, 800#, 1200#, 2000#, 3000#, and 5000# sandpaper. The polished sample is ultrasonically cleaned for 20 minutes, dried, and then placed on a 1×10 -3 s -1 The strain rate was set to 0.01, and Zr 33.5 Ti 28.5 Nb 19.0 Al 12 Ta 7.0Multi-component refractory intermetallic compounds.
[0050] The Zr obtained in Example 1 33.5 Ti 28.5 Nb 19.0 Al 12 Ta 7.0 Multi-component refractory intermetallic compounds are tested for performance. Figure 1 Example 1 Zr 33.5 Ti 28.5 Nb 19.0 Al 12 Ta 7.0 The scanning electron microscope micrograph of the multi-component refractory intermetallic compound after 90% cold rolling annealing shows that the multi-component refractory intermetallic compound can be subjected to large deformation microstructure control in the as-cast state. After annealing, the alloy microstructure is dense and the grain size is uniformly distributed. Statistics show that the grain size is 8.45±4.26 μm. Figure 2 is the corresponding XRD pattern of Example 1, Figure 3 The high-resolution and selected-area electron diffraction patterns of the multi-component refractory intermetallic compound of Example 1 after 90% homogenization treatment by cold rolling indicate that the structure thereof is a B2 intermetallic compound; Figure 4 This is a tensile engineering stress-engineering strain curve of the multi-component refractory intermetallic compound of Example 1 after 90% homogenization treatment by cold rolling. The alloy has a yield strength of 1174 MPa and a tensile elongation of 40.05% at room temperature.
[0051] Density was measured using the Archimedes displacement method. 6×6×6 mm block specimens were uniformly cut from the as-cast specimens. Before measurement, they were ultrasonically cleaned at room temperature for 30 min to remove surface dirt and impurities, and then dried in a drying oven. The dry weight M1 of each specimen was measured five times to reduce measurement error. The mass M2 of each specimen in water was then measured five times. Finally, the density was calculated using the following formula:
[0052]
[0053] Where, ρ 0 is the temperature of water, 0.9982g / cm 3 (293K); ρ 1 is the density of air, 0.0012g / cm 3 The average value of the three measurements is ρ =6.696g / cm 3 . Example 2
[0054] This embodiment designs a high-strength, light-weight, multi-component refractory intermetallic compound with the chemical formula Zr 33.5Ti 28.5 Nb 19.0 Al 12 Ta 7.0 (atomic percentage), the preparation steps are as follows:
[0055] (1) Raw material pretreatment: Zr, Nb, and Ta particles with a purity of ≥99.90 wt%, and Ti and Al particles with a purity of 99.95 wt% were polished and ultrasonically cleaned at room temperature for 30 min to remove surface dirt and impurities, and finally placed in a drying oven for drying.
[0056] (2) Raw material ratio: by converting the molar percentage and mass percentage of the multi-component refractory intermetallic compound, based on 100g of alloy, 39.321g, 17.609g, 22.933g, 4.167g and 16.060g of each metal raw material were weighed according to Zr, Ti, Nb, Al and Ta, respectively.
[0057] (3) Melting: Place the raw materials weighed in step 2 into the water-cooled copper crucible of the vacuum arc furnace in order of melting point. Note that the Al particles with low melting point are placed at the bottom. Vacuum to 5×10 -3 Pa, repeated three times; filled with argon to 0.05 MPa as a protective atmosphere; before smelting, melt the extra Ti ingots pre-placed in the furnace for 120 seconds to consume the residual oxygen and nitrogen in the smelting furnace, the smelting current is 330A, and the smelting time is 120 seconds; start smelting the alloy ingot, and smelt it repeatedly for 8 times. The smelting current is controlled at 390A, and each smelting arc should last for 7 minutes and be supplemented by electromagnetic stirring technology. The current frequency is 7Hz to ensure that the alloy is fully mixed.
[0058] (4) Casting: Place the evenly smelted alloy in a water-cooled copper mold of 80×30×10 mm in a vacuum arc furnace for remelting and molding. After the sample cools down, take out the sample. The specific operation is: vacuum to 5×10 -3 Pa, repeated three times; filled with argon to 0.05MPa as a protective atmosphere; melted the extra Ti ingots pre-placed in the furnace before smelting, the smelting current was 330A, and the smelting time was 120 seconds; started to smelt the alloy ingot, and smelted it repeatedly for 4 times, the smelting current was controlled at 390A, and the arc should last for 8 minutes each time.
[0059] (5) Cold rolling annealing: The cast alloy was cut into 9.5 mm thick strip samples, with a single-pass rolling reduction of ~10% and a total rolling reduction of 70%. The rolled sample was placed in a quartz tube and prepared for sealing. The quartz tube was first vacuumed to 3×10 -3Pa, and then filled with argon to maintain the pressure in the tube at 0.003 MPa. After the sealing is completed, the sample is kept at 850 ° C for 30 minutes and then immediately water quenched; the sample is cut into 1.50 × 7.5 × 21 mm dog bone tensile specimens by wire cutting, and polished on 180#, 400#, 800#, 1200#, 2000#, 3000#, and 5000# sandpaper. The polished sample is ultrasonically cleaned for 30 minutes, dried, and then placed on a 1×10 -3 s -1 Stretching was performed at a strain rate of .
[0060] Figure 5 Example 2 Zr 33.5 Ti 28.6 Nb 19.1 Al 12 Ta 6.9 The scanning electron microscope micrograph of the lightweight multi-component refractory intermetallic compound was obtained after being held at 850℃ for 30 minutes and then immediately water quenched. It can be seen that after the cold rolling and annealing treatment, the alloy structure is dense, and the grains are relatively large and evenly distributed. Figure 6 Example 2 Zr 33.5 Ti 28.6 Nb 19.1 Al 12 Ta 6.9 Homogeneous tensile engineering stress-engineering strain curve of a lightweight multi-component refractory intermetallic compound. After vacuum annealing, the alloy exhibits a tensile yield strength of 1180 MPa and a tensile elongation of 36.62%. Example 3
[0061] This embodiment designs a high-strength, light-weight, multi-component refractory intermetallic compound with the chemical formula Zr 32.75 Ti 28.25 Nb 18.75 Al 13 Ta 6.75 (atomic percentage), the preparation steps are as follows:
[0062] (1) Raw material pretreatment: Nb, Zr, and Ta particles with a purity of ≥99.90 wt%, and Ti and Al particles with a purity of 99.95 wt% were ultrasonically cleaned at room temperature for 30 min to remove surface dirt and impurities, and finally placed in a drying oven for drying.
[0063] (2) Raw material ratio: By converting the molar percentage and mass percentage of the lightweight, high-strength, lightweight multi-component refractory intermetallic compound, based on 100g of alloy, 38.862g, 17.473g, 22.071g, 4.548g and 15.925g of each metal raw material are weighed according to Zr, Ti, Nb, Al and Ta, respectively.
[0064] (3) Melting: Place the raw materials weighed in step 2 into the water-cooled copper crucible of the vacuum arc furnace in order of melting point. Note that the Al particles with low melting point are placed at the bottom. Vacuum to 5×10 -3 Pa, repeated three times; filled with argon to 0.05 MPa as a protective atmosphere; before smelting, melt the extra Ti ingots pre-placed in the furnace for 120 seconds to consume the residual oxygen and nitrogen in the smelting furnace, and the smelting current is 330A; start smelting the alloy ingot, and smelt it repeatedly for 6 times. The smelting current is controlled at 390A. Each smelting arc should last for 8 minutes and be supplemented by electromagnetic stirring technology. The current frequency is 7Hz to ensure that the alloy is fully mixed.
[0065] (4) Casting: The uniformly smelted alloy is placed in a water-cooled copper mold of 80×30×10 mm in a vacuum arc furnace for remelting and molding. After the sample cools down, the sample is taken out. The specific operation is to vacuum to 5×10 -3 Pa, repeated three times; filled with argon to 0.05MPa as a protective atmosphere; before melting, melt the extra Ti ingot pre-placed in the furnace for 120 seconds, the melting current is 330A; start melting the alloy ingot, repeat the melting 4 times, the melting current is controlled at 390A, and each melting arc should last 8min.
[0066] (5) Cold rolling annealing: The cast alloy was cut into 10.0 mm thick strip samples, with a single-pass rolling reduction of ~10% and a total rolling reduction of 80%. The rolled sample was placed in a quartz tube and prepared for sealing. The quartz tube was first vacuumed to 3.0 × 10 -3 Pa, and then filled with argon to maintain the pressure in the tube at 0.03 MPa. After the sealing is completed, the sample is kept at 900 ° C for 10 minutes and then immediately water quenched; the sample is cut into 1.0 × 7.5 × 21 mm dog bone tensile specimens by wire cutting, and polished on 180#, 400#, 800#, 1200#, 2000#, 3000#, and 5000# sandpaper. After polishing, it is ultrasonically cleaned in a beaker for 30 minutes, dried, and then placed in a 1×10 -3 s -1 Stretching was performed at a strain rate of .
[0067] The Zr obtained in Example 3 32.75 Ti 28.25 Nb 18.75 Al 13 Ta 6.75 Multi-component refractory intermetallic compounds are tested for performance. Figure 7 Example 3 Zr 32.75 Ti 28.25 Nb 18.75 Al 13 Ta 6.75The scanning electron microscope micrograph of the multi-component refractory intermetallic compound was obtained after cold rolling 80%, holding at 900℃ for 10min and then immediately water quenching. It can be seen that after cold rolling and annealing, the equiaxed grains are uniformly distributed. Figure 8 The corresponding XRD pattern of Example 3 shows that its structure is an intermetallic compound of B2; Figure 9 Example 3 Zr 32.75 Ti 28.25 Nb 18.75 Al 13 Ta 6.75 Homogeneous tensile engineering stress-engineering strain curve of a multi-component refractory intermetallic compound. The alloy exhibits a tensile yield strength of 1252 MPa and a room temperature tensile elongation of 35.7%.
[0068] Density was measured using the Archimedes displacement method. 6×6×6 mm block specimens were uniformly cut from the as-cast specimens. Before measurement, they were ultrasonically cleaned at room temperature for 30 min to remove surface dirt and impurities, and then dried in a drying oven. The dry weight M1 of each specimen was measured five times to reduce measurement error. The mass M2 of each specimen in water was then measured five times. Finally, the density was calculated using the following formula:
[0069]
[0070] Where, ρ 0 is the temperature of water, 0.9982g / cm 3 (293K); ρ 1 is the density of air, 0.0012g / cm 3 The average value of the three measurements is ρ =6.626g / cm 3 . Example 4
[0071] This embodiment is designed to use a high-strength, lightweight, multi-component refractory intermetallic compound with the chemical formula Zr 33.3 Ti 29.0 Nb 19.50 Al 11 Ta 7.2 (atomic percentage), the preparation steps are as follows:
[0072] (1) Raw material pretreatment: Nb, Zr, and Ta particles with a purity of ≥99.90 wt%, and Ti and Al particles with a purity of 99.95 wt% were ultrasonically cleaned at room temperature for 20 min to remove surface dirt and impurities, and finally placed in a drying oven for drying.
[0073] (2) Raw material ratio: By converting the molar percentage and mass percentage of the lightweight, high-strength, lightweight multi-component refractory intermetallic compound, based on 100g of alloy, 38.752g, 17.473g, 35.071g, 2.812g and 5.912g of each metal raw material are weighed according to Zr, Ti, Nb, Al and Ta, respectively.
[0074] (3) Melting: Place the raw materials weighed in step 2 into the water-cooled copper crucible of the vacuum arc furnace in order of melting point. Note that the Al particles with low melting point are placed at the bottom. Vacuum to 5×10 -3 Pa, repeated three times; filled with argon to 0.05 MPa as a protective atmosphere; before smelting, melt the extra Ti ingots pre-placed in the furnace for 120 seconds to consume the residual oxygen and nitrogen in the smelting furnace, and the smelting current is 330A; start smelting the alloy ingot, and smelt it repeatedly for 6 times. The smelting current is controlled at 390A. Each smelting arc should last for 8 minutes and be supplemented by electromagnetic stirring technology. The current frequency is 7Hz to ensure that the alloy is fully mixed.
[0075] (4) Casting: The uniformly smelted alloy is placed in a water-cooled copper mold of 80×30×10 mm in a vacuum arc furnace for remelting and molding. After the sample cools down, the sample is taken out. The specific operation is to vacuum to 5×10 -3 Pa, repeated three times; filled with argon to 0.05MPa as a protective atmosphere; before melting, melt the extra Ti ingot pre-placed in the furnace for 120 seconds, the melting current is 320A; start melting the alloy ingot, repeat the melting 4 times, the melting current is controlled at 390A, and each melting arc should last 7min.
[0076] (5) Cold rolling annealing: The cast alloy was cut into 10.6 mm thick strip samples, with a single-pass rolling reduction of ~8% and a total rolling reduction of 80%. The rolled sample was placed in a quartz tube and prepared for sealing. The quartz tube was first vacuumed to 3.0 × 10 -3 Pa, and then filled with argon to maintain the pressure in the tube at 0.003 MPa. After the sealing is completed, the sample is kept at 850 ° C for 30 minutes and then immediately water quenched; the sample is cut into 1.5 × 7.5 × 21 mm dog bone tensile specimens by wire cutting, and polished on 180#, 400#, 800#, 1200#, 2000#, 3000#, and 5000# sandpaper. After polishing, it is ultrasonically cleaned in a beaker for 30 minutes, dried, and then placed in a 1×10 -3 s -1 Stretching was performed at a strain rate of .
[0077] The Zr obtained in Example 4 33.3 Ti 29.0 Nb 19.50 Al 11 Ta7.2 Multi-component refractory intermetallic compounds are tested for performance. Figure 10 Example 4 Zr 33.3 Ti 29.0 Nb 19.50 Al 11 Ta 7.2 The high-strength and tough multi-component refractory intermetallic compound was cold rolled 80%, kept at 850℃ for 30min and then immediately water quenched to obtain the scanning electron microscope micrograph. It can be seen that after the cold rolling and annealing treatment, the equiaxed grains are uniformly distributed. Figure 11 The corresponding XRD pattern of Example 3 shows that its structure is an intermetallic compound of B2; Figure 12 Example 3 Zr 33.3 Ti 29.0 Nb 19.50 Al 11 Ta 7.2 Homogeneous tensile engineering stress-engineering strain curve of a multi-component refractory intermetallic compound. The alloy exhibits a tensile yield strength of 1018 MPa and a room temperature tensile elongation of 35.1%.
[0078] Density was measured using the Archimedes displacement method. 6×6×6 mm block specimens were uniformly cut from the as-cast specimens. Before measurement, they were ultrasonically cleaned at room temperature for 30 min to remove surface dirt and impurities, and then dried in a drying oven. The dry weight M1 of each specimen was measured five times to reduce measurement error. The mass M2 of each specimen in water was then measured five times. Finally, the density was calculated using the following formula:
[0079]
[0080] Where, ρ 0 is the temperature of water, 0.9982g / cm 3 (293K); ρ 1 is the density of air, 0.0012g / cm 3 The average value of the three measurements is ρ =6.795g / cm 3 . Comparative Example 1
[0081] According to the chemical formula Zr 31.0 Ti 28.0 Nb 19 Al 16 Ta 6.0 (atomic percentage) for the ingredients, Nb, Ti, Zr, Ta and Al raw materials use their corresponding single substance particles (purity ≥ 99.95%). Wait until the pressure in the vacuum suspension furnace is pumped to 5×10 -3After Pa, an inert gas was filled in. Under the protection of the inert gas, the alloy sample was repeatedly turned over and smelted 6 times, and then cast to obtain a casting billet, which was the alloy in Comparative Example 1.
[0082] Figure 13 This is the macroscopic morphology of the comparative alloy after rolling. The alloy cracked during rolling deformation.
[0083] The present invention provides a high-strength, tough, lightweight, multi-component refractory intermetallic compound with uniform structure. It does not require intermediate annealing treatment and can be directly subjected to large deformation cold rolling to control the structure. The process flow is simple and energy consumption and cost are significantly reduced.
[0084] The present invention achieves a room temperature elongation of up to 10.0-45.0% and a room temperature yield strength of 900-1400 MPa in a lightweight multi-component refractory intermetallic compound by designing the ratio of Nb, Ti, Zr, Ta and Al elements. The strong plasticity matching combination can be directly cold rolled and short-time annealed at room temperature to achieve microstructure control, which is conducive to deformation processing and can realize the preparation of large-size samples. The reasonable selection of Al element ratio can obtain a high density. ρ =6.20~7.00g / cm³ lightweight multi-component refractory intermetallic compounds; addressing the inherent brittleness and poor room-temperature deformability of traditional TiAl-based intermetallic compounds. Focusing on refractory elements from Groups IVB, VB, and VIB (all with melting points above 1600°C), and introducing innovative design concepts for multi-component alloys, the developed ZrTiNbAlTa-based high-strength, lightweight, multi-component refractory intermetallic compounds exhibit high specific strength, low density, high oxidation resistance, and good creep resistance. They can be used in heat-resistant components for the aviation, aerospace, and automotive industries, and possess excellent room-temperature deformability. They are particularly suitable for forming complex, thin-walled components, enabling the production of precision, complex components with zero or near-zero allowance, significantly reducing metal loss, improving material utilization, and eliminating extensive machining, significantly lowering production costs.
[0085] This patent designs a high-strength, lightweight, multi-component refractory intermetallic compound through element design, composition ratio and the introduction of low-density elements, giving it the potential to serve in high-temperature environments such as aerospace.
[0086] It should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention and are not intended to limit the present invention. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solutions of the present invention may be modified or replaced by equivalents without departing from the spirit and scope of the technical solutions of the present invention, which should all be included in the scope of the claims of the present invention.
Claims
1. A high-strength, light-weight, multi-component refractory intermetallic compound, characterized in that: The intermetallic compound is an intermetallic compound B2 structure in any state, and the intermetallic compound is designed to include, by atomic percentage, Zr 32.75-33.5%, Ti 28.25-29%, Nb 18.75-19.5%, Al 11-13%, and Ta 6.75-7.2%; The sum of the atomic percentages of each component is 100%; Weighing each component according to the atomic ratio of the intermetallic compound, melting it under vacuum or inert gas protection conditions, casting it, cold-rolling the cast intermetallic compound, and then annealing it under vacuum or protective atmosphere; The cold rolling deformation is performed by performing multiple large deformation rolling processes, with a single-pass rolling reduction of ≤20% and a total rolling reduction of 70% to 100%; The annealing treatment has an annealing temperature of 850-900° C. and an annealing time of 10-30 min, followed by immediate quenching.
2. The method for preparing a high-strength, light-weight, multi-component refractory intermetallic compound according to claim 1, characterized in that: include, Weighing each component according to the atomic ratio of the intermetallic compound, melting it under vacuum or inert gas protection conditions, casting it, cold-rolling the cast intermetallic compound, and then annealing it under vacuum or protective atmosphere; The cold rolling deformation is performed by performing multiple large deformation rolling processes, with a single-pass rolling reduction of ≤20% and a total rolling reduction of 70% to 100%; The annealing treatment has an annealing temperature of 850-900° C. and an annealing time of 10-30 min, followed by immediate quenching.
Citation Information
Patent Citations
ZrTiNbAlTa refractory high-entropy alloy with low neutron absorption section and preparation method of ZrTiNbAlTa refractory high-entropy alloy
CN113549805A
Al-containing refractory high-entropy alloy and preparation method thereof
CN114535576A
Lightweight refractory multi-principal element alloy and preparation method and application thereof
CN115627406A
Lightweight high-strength multi-component refractory alloy with ultrahigh room-temperature tensile ductility and preparation method of lightweight high-strength multi-component refractory alloy
CN116497257A
Refractory metal based multi-component alloy for articulating surfaces in total joint arthroplasty
IN201931008558A
